European demonstration program on the effect-based and chemical identification and monitoring of organic pollutants in European surface waters - Tousova, Zuzana; Oswald, Peter; Slobodnik, Jaroslav; Blaha, Ludek; Muz, Melis; Hu, Meng; Brack, Werner; Krauss, Martin; Di Paolo, Carolina; Tarcai, Zsolt; Seiler, Thomas-Benjamin; Hollert, Henner; et al. (The Science of the total environment, 2017)
Growing concern about the adverse environmental and human health effects of a wide range of micropollutants requires the development of novel tools and approaches to enable holistic monitoring of their occurrence, fate and effects in the aquatic environment. A European-wide demonstration program (EDP) for effect-based monitoring of micropollutants in surface waters was carried out within the Marie Curie Initial Training Network EDA-EMERGE. The main objectives of the EDP were to apply a simplified protocol for effect-directed analysis, to link biological effects to target compounds and to estimate their risk to aquatic biota. Onsite large volume solid phase extraction of 50 L of surface water was performed at 18 sampling sites in four European river basins. Extracts were subjected to effect-based analysis (toxicity to algae, fish embryo toxicity, neurotoxicity, (anti-)estrogenicity, (anti-)androgenicity, glucocorticoid activity and thyroid activity), to target analysis (151 organic micropollutants) and to nontarget screening. The most pronounced effects were estrogenicity, toxicity to algae and fish embryo toxicity. In most bioassays, major portions of the observed effects could not be explained by target compounds, especially in case of androgenicity, glucocorticoid activity and fish embryo toxicity. Estrone and nonylphenoxyacetic acid were identified as the strongest contributors to estrogenicity, while herbicides, with a minor contribution from other micropollutants, were linked to the observed toxicity to algae. Fipronil and nonylphenol were partially responsible for the fish embryo toxicity. Within the EDP, 21 target compounds were prioritized on the basis of their frequency and extent of exceedance of predicted no effect concentrations. The EDP priority list included 6 compounds, which are already addressed by European legislation, and 15 micropollutants that may be important for future monitoring of surface waters. The study presents a novel simplified protocol for effect-based monitoring and draws a comprehensive picture of the surface water status across Europe.
Keywords: EDA-EMERGE; Adverse effects; Environmental health; Human health; Large volume solid phase extraction; Simplified effect-directed analysis protocol